EL BARROCO ANDALUZ Y LOS MODELOS DEL BARROCO ITALIANO - Rivas Carmona, Jesús; Cabello Velasco, Rafaela (Imafronte, 1993)
Beside certain pure and peculiar characteristics, the urge for decoration amot~g them, the Andalusian Baroque shows other cosmopolitan features linking it to the international Baroque. It is to consider its relationships with Italian formulae. There are curious parallelisms concerning the use of the central ground. and some enthusiasm for using the curve or other borrominesque elements (for example, many of the motives employed in Sevilla by Leonardo de Figueroa). Treatises and their illusrrations are an important source to know Italian art; in fact, it is clear from documents that artists and architects owned this kind of works. Some of these masters possessed not oniy books by the 16th century classics, but also by baroque authors. Guarino Guarini's printed work inspired different productions; sometimes, he was so accurately followed that it is not to be surprised because of the great similarity between the Italian's work in the tabernacle of St. Nicholas of Verona and what was done in the Sacrarium tabernacle of the Cathedral of Granada. This is a confirmation of the use of the mentioned treatises.